Mapping The Global Research Landscape Of Destination Branding And Ecotourism (2014–2024): A Bibliometric Analysis - Muhammad Rizki Ridani; Herlina Agustin; Yustikasari (INJECT (Interdisciplinary Journal of Communication), 2025)
This study aims to map the scholarly development of research on the integration of destination branding and ecotourism within global literature from 2014 to 2024. Using a bibliometric analysis based on Scopus data, the study traces publication trends, author and journal productivity, country level collaboration, and the thematic structures that emerge in international research. A total of 205 articles meeting the selection criteria were analyzed using Biblioshiny in the Bibliometrix package in R Studio, following stages of data cleaning, metadata standardization, and keyword as well as citation-network mapping. The findings indicate a significant rise in publications connecting destination branding with ecotourism, with the highest growth recorded in 2024. Keywords such as ecotourism, destination image, and sustainable tourism dominate the thematic network, while the thematic map reveals three major clusters: the integration of branding and sustainability, tourist experiences and emotional attachment, and the role of ecotourism in shaping destination image. These findings suggest that global research is shifting toward a multidisciplinary approach that positions conservation, local identity, and ecological experience as essential components of destination branding. Nevertheless, methodological limitations such as reliance on metadata, language constraints, and the use of a single database restrict the generalizability of the results. Thus, this study offers an initial overview of the knowledge structure in this field and opens avenues for further research that combines bibliometrics with content analysis to gain a more comprehensive understanding of its conceptual dynamics.